The Auditor’s Use of Third Party Work Based on the Supply Chain Strategy - Anna Vladimirovna Kravtsova; Julietta Vladimirovna Khachaturova; Aleksey Fedorovich Kolabasov (International Journal of Supply Chain Management, 2019)
In current conditions of entrepreneurship development, the role of audit committees in verifying companies’ financial and economic activities is increasing, which can be more efficient by using supply chain strategy in organization. The authors aim to attract the attention of external auditors to the work performed by the company’s inspectors as third parties.The competence of the audit committee members determines the reduction of business risks, in particular, the threat of pursuingactivities and tax risks;the improvement ofthe quality of information material for management structures, the reliability of internal reports and financial (accounting) statements; compliance with the dividend policy and many other issues.The auditors should rely on the experience of competent members of the audit committee, which is expressed in various official, policy briefs, reports and audit opinion. The auditor must verify the audit committee’s competence by conducting various procedures that are documented in accordance with the internal rules (standards) of the audit organization.The authors use such research methods as analysis, synthesis, observation, experiment, based on their theoretical knowledge and developments, participation as auditors in audits, experience in management and relationship director – auditor in the company. The study allows the authors to provide guidance on the development and documentation of relations between auditors and members of the company’s audit committee, increasing auditors’responsibility in reviewing and using third party work in their findings, as their conclusions can affect the type of an audit report under formation.The scientific novelty consists in developing the idea of the need and relevance of assessing the extent to which auditors use the results of the work of members of the company’s audit committee, since now auditors do not use audit reports for a deeper understanding of the company activities and reducing audit risk. The relationship between auditors and the audit committee members is not regulated by the existing standards, which should be the subject of further research on auditors’activities to revise Russian companies operating in accordance with the Federal Law No. 14-FZ.